2020
DOI: 10.3389/fcell.2020.00647
|View full text |Cite
|
Sign up to set email alerts
|

Are Epithelial Ovarian Cancers of the Mesenchymal Subtype Actually Intraperitoneal Metastases to the Ovary?

Abstract: Primary ovarian high-grade serous carcinoma (HGSC) has been classified into 4 molecular subtypes: Immunoreactive, Proliferative, Differentiated, and Mesenchymal (Mes), of which the Mes subtype (Mes-HGSC) is associated with the worst clinical outcomes. We propose that Mes-HGSC comprise clusters of cancer and associated stromal cells that detached from tumors in the upper abdomen/omentum and disseminated in the peritoneal cavity, including to the ovary. Using comparative analyses of multiple transcriptomic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Consistent with our enriched tumor and stroma cell findings, single-cell RNA sequencing on HGSOCs has previously revealed that individual cells of the same tissue type (tumor epithelium or stroma) differentially clustered with molecular subtypes due to unique gene expression profiles (Winterhoff et al, 2017). Further, heterogeneity within HGSOC molecular subtypes has been partially attributed to activation of distinct transcription factors serving as master regulators of the cellular phenotypes (Zhang et al, 2015;Eckert et al, 2019), as well as re-seeding of the primary site of disease by intraperitoneal metastases (Hu et al, 2020). As mentioned, within the ovarian stromal microenvironment, we observed the highest probability of classification as mesenchymal and/or immunoreactive subtypes (Figure 5).…”
Section: Access Isciencesupporting
confidence: 52%
“…Consistent with our enriched tumor and stroma cell findings, single-cell RNA sequencing on HGSOCs has previously revealed that individual cells of the same tissue type (tumor epithelium or stroma) differentially clustered with molecular subtypes due to unique gene expression profiles (Winterhoff et al, 2017). Further, heterogeneity within HGSOC molecular subtypes has been partially attributed to activation of distinct transcription factors serving as master regulators of the cellular phenotypes (Zhang et al, 2015;Eckert et al, 2019), as well as re-seeding of the primary site of disease by intraperitoneal metastases (Hu et al, 2020). As mentioned, within the ovarian stromal microenvironment, we observed the highest probability of classification as mesenchymal and/or immunoreactive subtypes (Figure 5).…”
Section: Access Isciencesupporting
confidence: 52%
“…The mesenchymal subtype is characterized by desmoplasia and enrichment in myofibroblasts expressing COL11A1, α-SMA, and PDPN. The mesenchymal phenotype of metastases is likely a reflection of the tumor location (ovary/adnexa in the pelvis vs. omentum/peritoneum in the upper abdomen) rather than differences between primary tumors and metastases because the majority of primary peritoneal carcinomas (PPC) are classified as the mesenchymal subtype [ 59 ] and there is evidence that mesenchymal primary tumors may actually be PPC metastases to the ovary [ 60 ] or secondary metastases to the ovary [ 61 , 62 ]. Together, these results suggest that the mesenchymal phenotype is determined by the metastatic microenvironment rather than by the intrinsic molecular subtype of epithelial cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The training dataset was the GSE26712 ( Bonome et al, 2008 ) cohort ( n = 182). Validation cohorts were the TCGA( Cancer Genome Atlas Research Network, 2011 ) ( n = 578), GSE9891 ( Tothill et al, 2008 ) ( n = 285), ICGC-AU ( Patch et al, 2015 ) ( n = 111), GSE138866 ( Hu et al, 2020 ) ( n = 130), GSE32062 ( Yoshihara et al, 2012 ) ( n = 260), GSE14764 ( Denkert et al, 2009 ) ( n = 80), and GSE51088 ( Karlan et al, 2014 ) ( n = 172) datasets. Together with the corresponding clinical information, the normalized expression datasets sourced from the GEO database were downloaded via the GEOquery package (version 2.58.0).…”
Section: Methodsmentioning
confidence: 99%